Enhanced Inhibition of Tumorigenesis Using Combinations of miRNA-Targeted Therapeutics - Miroshnichenko, Svetlana; Patutina, Olga (Frontiers in Pharmacology, 2019)
The search for effective strategies to inhibit tumorigenesis remains one of the most relevant scientific challenges. Among the most promising approaches is the direct modulation of the function of short non-coding RNAs, particularly miRNAs. These molecules are propitious targets for anticancer therapy, since they perform key regulatory roles in a variety of signaling cascades related to cell proliferation, apoptosis, migration, and invasion. The development of pathological states is often associated with deregulation of miRNA expression. The present review describes in detail the strategies aimed at modulating miRNA activity that invoke antisense oligonucleotide construction, such as small RNA zippers, miRNases (miRNA-targeted artificial ribonucleases), miRNA sponges, miRNA masks, anti-miRNA oligonucleotides, and synthetic miRNA mimics. The broad impact of developed miRNA-based therapeutics on the various events of tumorigenesis is also discussed. Above all, the focus of this review is to evaluate the results of the combined application of different miRNA-based agents and chemotherapeutic drugs for the inhibition of tumor development. Many studies indicate a considerable increase in the efficacy of anticancer therapy as a result of additive or synergistic effects of simultaneously applied therapies. Different drug combinations, such as a cocktail of antisense oligonucleotides or multipotent miRNA sponges directed at several oncogenic microRNAs belonging to the same/different miRNA families, a mixture of anti-miRNA oligonucleotides and cytostatic drugs, and a combination of synthetic miRNA mimics, have a more complex and profound effect on the various events of tumorigenesis as compared with treatment with a single miRNA-based agent or chemotherapeutic drug. These data provide strong evidence that the simultaneous application of several distinct strategies aimed at suppressing different cellular processes linked to tumorigenesis is a promising approach for cancer therapy.